Nickel electrodeposition using deep eutectic solvent-based electrolyte - Dela Peña, Eden May B. (2023)
While nickel (Ni) electroplating has been successfully performed using ionic liquids in the past, few studies have reported on the trench-filling characteristics of this process useful for electroforming Ni. This study aimed to deposit and characterize the electrodeposited nickel using an ethaline-based nickel-plating bath with and without ethylenediamine (en). The conductivity of the plating bath was improved, while viscosity was slightly reduced upon the addition of en. Cyclic and linear sweep voltammetry revealed that en acted as a suppressor, significantly reducing the bath’s plating rate. The Hull cell was used to determine the optimum operating current density for each bath. The additive-bearing bath produced more compact deposits, better deposit grain morphology, and improved trench-filling (> 95% filling) characteristics compared to its additive-free counterpart. The enhanced super-filling characteristics may be explained by the differential acceleration curvature-enhanced accumulation acceleration (CEAC) model. SEM analysis showed that the deposits possessed a particulate or nodular structure, whereas EDS confirmed the presence of Ni in the deposit. The Ni deposited using the bath without additives had larger particulate grains than those using the additive-bearing bath. Higher Ni amounts were obtained in the additive-laden bath. The use of additives is a promising approach for improving the super-filling characteristics of ionic liquid plating baths.
Keywords: Nickel; Electrolytes